-2x-6=30-6x

Simple and best practice solution for -2x-6=30-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x-6=30-6x equation:



-2x-6=30-6x
We move all terms to the left:
-2x-6-(30-6x)=0
We add all the numbers together, and all the variables
-2x-(-6x+30)-6=0
We get rid of parentheses
-2x+6x-30-6=0
We add all the numbers together, and all the variables
4x-36=0
We move all terms containing x to the left, all other terms to the right
4x=36
x=36/4
x=9

See similar equations:

| 3v-19=44 | | 5x+58=7x+50 | | 3a-4a=a | | 2x+6=3x+6=90 | | x+3+x−8+x=55. | | 2u-25=9 | | a=102a+3 | | |5-x|=26 | | (5/2)a-(a+4)=a+10 | | 9−2t=3 | | 38x-1+3+51x=180 | | 4x+28+90+5x-1=180 | | 38x-1=3+51x | | 9(u-94)=45 | | 83+x=78 | | -7(b-85)=-42 | | 3h+34=88 | | 33=7u-23 | | 4(c-76)=52 | | 2k-6+3k=18 | | 3x-13+90+5x-9=180 | | 24-3d=18 | | 9(b+1)=90 | | 3x−52=14 | | 0=14-9.8×t | | x+3+84=90 | | 23-7(x-3)=5x+10 | | 9(b+4)=90 | | 3(x-6)-8x=-2+5(2x+) | | 5(t-80)=10 | | F(x)=2/5+24 | | w+20/5=6 |

Equations solver categories